A historical analysis of the economic development of the USA (1947-2017) - Şenel Uzunkaya, Seçil; Dinçer, Hasan; Yüksel, Serhat (My University, 2019)
The aim of this study is to evaluate economic improvement of the USA. For this purpose, the quarterly data for the periods between 1947 and 2017 is taken into the consideration. Therefore, focusing on this long period provides a historical view so that more appropriate results can be achieved. Moreover, economic growth of the USA is considered as dependent variable whereas four different subtitles of GDP (consumption, private investment, government expenditure and net export) are selected as independent variables. Furthermore, multivariate adoptive regression spline (MARS) methodology is used in the analysis process. The findings show that private investment, government expenditure and net export have a positive relationship between economic growth. It is identified that the positive effect reduces when the percentage of government expenditure exceeds 22.2%. On the other side, in case of negative net export and having lower investment ratio than 16.3%, economic development of US will be affected negatively. These results give very important information that instead of consumption, other three subtitles of GDP make a contribution to the economic development of US. By considering these results, it is recommended that US should mainly implement growth strategies by focusing on private investment and net export. Within this framework, tax advantages for these investors can be provided to reach this objective. In addition to this condition, government should also give incentives to improve industrial production so that investment and export can be increased.

Bu çalışmanın amacı ABD'nin ekonomik gelişiminin tarihsel bir bakış açısıyla değerlendirilmesidir. Bu amaçla, 1947 ve 2017 arasındaki dönemler için üç aylık veriler dikkate alınmıştır. Bu nedenle, bu uzun döneme odaklanarak daha uygun sonuçların elde edilebilmesi için tarihsel bir analiz yapılması amaçlanmıştır. Ayrıca ABD'nin ekonomik büyüme oranı bağımlı değişken olarak kabul edilirken, GSYİH'nin dört farklı alt başlığı (tüketim, özel yatırım, devlet harcamaları ve net ihracat) bağımsız değişkenler olarak seçilmiştir. Öte yandan, analiz sürecinde çok değişkenli uyumlu regresyon uzanımları (MARS) metodolojisi kullanılmıştır. Bulgular, özel yatırım, hükümet harcamaları ve net ihracatın ekonomik büyüme arasında pozitif bir ilişki olduğunu göstermektedir. Belirtilen hususa ek olarak, devlet harcamalarının oranı % 22.2'yi aştığında olumlu etkinin azaldığı tespit edilmiştir. Öte yandan, net ihracatın negatif olması ve % 16.3'den daha düşük bir yatırım oranı olması durumunda, ABD'nin ekonomik gelişimi olumsuz yönde etkilenecektir. Bu sonuçlar, tüketim yerine GSYİH'nin diğer üç alt bileşenlerinin ABD'nin ekonomik gelişimine katkı sağladığına dair çok önemli bilgiler vermektedir. Bu sonuçları göz önünde bulundurarak, ABD'nin özellikle özel yatırımlara ve ihracata odaklanarak büyüme stratejilerini uygulamaya koyması önerilmektedir. Bu çerçevede, bu hedefe ulaşmak için yatırımcılara vergi avantajlarının sağlanması yerinde olacaktır. Bu duruma ek olarak, hükümet ayrıca, sanayi üretimini iyileştirmek için teşvikler vererek yatırım ve ihracatın arttırılmasına olumlu etki edebilecektir.
ABD’nin ekonomik gelişmesinin tarihsel bir analizi (1947-2017)
Keywords: US Economy; GDP; Historical Analysis; Economic Development; MARS; ABD Ekonomisi; GSYİH; Tarihsel Analiz; Ekonomik Kalkınma